Development of a control system for multiple unmanned aerial vehicles - Andrey P. Preobrazhenskiy; Tatyana V. Avetisyan; Yuriy P. Preobrazhenskiy (International Journal of Advanced Studies)
Background. The study considers the problem associated with the development of a control system for many unmanned aerial vehicles. An analysis of the possibilities of improving the efficiency of control of unmanned aerial vehicle systems is carried out. The role of classification methods in the rating assessment of the system of flying objects is shown. The structure of interaction between the control center and a set of unmanned aerial vehicles is presented. A description of approaches related to the assignment of a rating is given. The control center maintains monitoring of the efficiency of the functioning of aircraft. It is shown how the various stages of rating management of a set of unmanned aerial vehicles are interconnected. The general integral assessment has an impact on the partial integral assessment. If the rating of the aircraft coincides with the maximum integral score, it will be considered as having the highest rating.